Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

There's a mapping $f:X\rightarrow Y$.

1.for all $A,B\subset X$, $f(A\cap B)=f(A)\cap f(B)$, prove $f$ is injective.

2.for all $A\subset X$, $f(A^{c})=[f(A)]^{c}$, prove $f$ is bijective.

share|improve this question
    
Try to show us what you have tried yourself, and where you got stuck. This way we can help you more effectively! You will also learn a lot more this way. –  sxd Sep 9 '12 at 15:05

2 Answers 2

up vote 4 down vote accepted

For 1 you want to show that $f(x) = f(y)$ implies $x = y$. So let $f(x) = f(y)$. Then $f(\{x\}) = f(\{y\})$ and hence $f(\{x\}) \cap f(\{y\}) = f(\{x\}) = f(\{y\}) = f(\{x\} \cap \{y\})$. Hence $x=y$.

share|improve this answer
    
Now try to do 2 in a similar way. –  Rudy the Reindeer Sep 9 '12 at 15:06

(1) Suppose $f$ is not injective. That is, there exists $a \neq b$ such that $f(a) = f(b)$. Consider the sets $\{a\}$ and $\{b\}$. Then $f(\{a\} \cap \{b\}) = f(\emptyset) = \emptyset \neq f(\{a\}) \cap f(\{b\})$.

(2) Suppose $f$ is not injective. Then there exists an $x$ such that $f^{-1}(x)$ contains more than a single element. Let $a \in f^{-1}(x)$. Let $A = f^{-1}(x) - \{a\}$. Then $x \in f(A^c)$ but $x \notin f(A)^c$. So $f(A^c) \neq f(A)^c$.

Suppose that $f$ is not surjective. Then there exists a $y \in Y$ such that $y \notin f(X)$. Let $A = X$. Then $f(A^c) = f(\emptyset) = \emptyset$. However $y \in f(A)^c$. Hence $f(A^c) \neq f(A)^c$.

Thus, it has been shown that $f$ is injective and surjective.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.